Experimental Study on Desorption Characteristics of Coalbed Methane under Variable Loading and Temperature in Deep and High Geothermal Mine - Haifeng Ma; Lingjie Wang; Housheng Jia; Jucai Chang; YingMing Li; Xiangyang Zhang; Zuxiang Hu; Zhiqiang Yin (Advances in Civil Engineering)
Due to the influence of deep high stress, geothermal heat, and other factors, the law of desorption of methane in coal seams is more complicated in the process of mining deep coal seams, which is prone to methane over-limit, coal and gas outburst, and other accidents. In order to study the desorption characteristics of coalbed methane under different loading and temperature conditions, the desorption tests at different deformation stages of coal containing methane were carried out in the process of loading-adsorption-desorption-reloading until the coal sample was destroyed by using the seepage-adsorption-desorption test system on coal and rock mass, and the test programs were different combinations of gas pressure 1.2 MPa, two kinds of confining pressure, and three kinds of temperature. The results show that the cumulative methane desorption amount corresponding to each deformation stage presents a convex parabolic increase trend with the increase in desorption time, while the desorption rate presents a power function decay trend. Under the condition of the same desorption time, the cumulative methane desorption amount from large to small is residual deformation stage, compaction stage, near the peak stress, plastic deformation stage, and elastic deformation stage. Under the same confining pressure, temperature, and methane pressure, the maximum desorption rate from large to small is residual deformation stage, near the peak stress, plastic deformation stage, compaction stage, and elastic deformation stage. The desorption and diffusion of methane are promoted under the higher temperature and lower confining pressure, which presents a certain mechanism of promoting desorption. The thermal movement of methane molecules is intensified with the increase in temperature, and the adsorption effect between methane molecules and the molecules at the surface of the coal is weakened. The cumulative methane desorption amount and the maximum desorption rate increase with the increase in temperature. The cumulative methane desorption in the residual deformation stage is obviously greater than that in other deformation stages. The increase in confining pressure inhibits the development and expansion of pore fractures in raw coal specimen and hinders the increase in the effective desorption surface area. The cumulative methane desorption amount and the maximum desorption rate decrease with the increase in confining pressure.